Konflik Tanah Perkebunan Di lndonesia - j sembiring (Jurnal Hukum IUS QUIA IUSTUM, 2006)
Land-ownership conflicts concerning estate rops are classical problems faced by the government (colonial or national). However, it has indicated an increase in the post-reformation era.According toits typology, thereare 5 aspects involved namely: subject, object, causalfactor, claim effort, and settlementef fort. This article puts forward an argu mentthat the conflicts arise because oflegal, political and psychological aspects. Non-litigation as a settlementef for thas tobe introduced and developed to solve the conflicts. More over, land administration systemhas to be managed by estate-crops corporations properly